2002
DOI: 10.1136/fn.86.2.f131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enteral administration of insulin on intestinal development and feeding tolerance in preterm infants: a pilot study

Abstract: These preliminary data suggest that enteral insulin administration may be of benefit in reducing feed intolerance in preterm infants. A randomised, blinded trial is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Available animal data, the presence of insulin in human milk (18,28), and the observation that oral administration of insulin to preterm infants (26-29 weeks of gestational age) increases lactase activity and reduces feeding intolerance (29) suggest that it is time to investigate the role of oral insulin supplementation in humans and its possible clinical implications.…”
Section: Discussionmentioning
confidence: 96%
“…Available animal data, the presence of insulin in human milk (18,28), and the observation that oral administration of insulin to preterm infants (26-29 weeks of gestational age) increases lactase activity and reduces feeding intolerance (29) suggest that it is time to investigate the role of oral insulin supplementation in humans and its possible clinical implications.…”
Section: Discussionmentioning
confidence: 96%
“…The evidence that oral INS has a trophic effect on intestinal mucosa comes from experiments by Shulman et al, who have demonstrated that oral INS stimulates an increase in ileal mass and disaccharidase activity (12) and increases ileal lactase activity (13) in the newborn miniature pig. In a recent clinical trial, Shulman showed that enteral administration of INS to preterm infants (26-29 weeks of gestational age) leads to higher lactase activity and less feed intolerance (22).…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous administration of interleukin-10 was used with variable outcomes in a small number of adults with refractory celiac disease [35]. In premature neonates, a single study involving 8 newborns evaluated the effects of enterally administered insulin on intestinal development and feeding intolerance and suggested that insulin might be of benefit in reducing feeding intolerance [36]. However, the minimal amounts and composition of growth factors as well as the routes of administration necessary to maintain specific intestinal functions in adults and neonates remain to be established.…”
Section: Discussionmentioning
confidence: 99%